New Magellanic penguin Spheniscus magellanicus colony in a subantarctic island - Raya Rey, Andrea Nélida; Balza, Ulises; Domato, Ignacio; Zunino, Francisco (Polar Biology)
This paper provides data on a newly discovered colony of Magellanic penguins Spheniscus magellanicus in the southwest Atlantic Ocean. A new settlement was found while conducting southern rockhopper penguin Eudyptes chrysocome studies in the San Juan de Salvamento colony in Staten Island, Argentina. The colony holds 88 breeding pairs. While the origin of the founders was unknown, it is possible that they came from the nearby Observatorio Island colony located ~ 20 km away. New colonies allow populations to expand and establish in new areas, which could allow a species to respond to changes in climate. Nonetheless, this expansion might be a detriment to other penguin species that already occupied the area. Fil: Raya Rey, Andrea Nélida. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego; Argentina. Wildlife Conservation Society; Estados Unidos Fil: Balza, Ulises. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Domato, Ignacio. Logistic Expedition; Argentina Fil: Zunino, Francisco. Logistic Expedition; Argentina. Ministerio de Ambiente y Desarrollo Sustentable. Administracion de Parques Nacionales. Direccion Regional Patagonia Austral - Sede Calafate; Argentina